"We Have To Make Sure That We Get It Right": Organizational Impression Management By a Police Service Confronted with Controversy - Lancia, Amanda (My University, 2023)
This dissertation explores the presentational strategies the Toronto Police Service (TPS) used to respond to three controversies involving its relationship with marginalized and racialized communities - the removal of the TPS from the Toronto Pride parade; the investigation of the serial killer case involving Bruce McArthur; and the Black Lives Matter protests of the summer of 2020. Using an interpretive approach and a variety of conceptual frameworks derived from Goffman’s work on impression management and applying a grounded theory methodology combined with qualitative media analysis (QMA), the dissertation identifies the image management strategies the TPS adopted in each case. The findings show that the strategies were context specific in the sense that they were directed to the precise criticisms being leveled at the TPS in each case. However, there were common themes across the cases which involved acknowledging a problematic past and committing to corrective actions in the future. The main difference in strategies had to do with the degree to which the TPS was prepared to push back on the claims made against the organization and defend its actions. The dissertation speaks to the broader question of how police organizations are attempting to negotiate their legitimacy in a climate where social media has made police-citizen encounters more visible and where recent high profile incidents involving police violence and abuse of power have shaken public confidence and threatened police legitimacy. I argue that taken together, the TPS responses offer a glimpse into how one police organization is seeking to defend its legitimacy by projecting an image of the kind of police service it is aspiring to become, particularly in relation to the marginalized and racialized communities it serves.
Keywords: Police; Impression Management; Organizational Image; Police Legitimacy; Qualitative Methods